THE IMPACT OF ETHICAL LEADERSHIP IN ORGANIZATIONS ON PERCEIVED STRESS AND JOB PERFORMANCE - ARSLAN, Ceylan; AVCI, Keziban (Göbeklitepe Medical Science Journal, 2022)
This study aimed to examine the impact of ethical leadership on perceived stress and job performance as per the literature. Ethical leaders' attitudes and behaviours in accordance with ethical principles and values have an impact on employee performance and perceived stress. In other words, employees in organizations led by managers who show ethical leadership have higher job performance and lower stress perceptions. In this respect, organizational productivity and employee satisfaction are observed to be high. To achieve this positive impact of ethical leaders on organizational productivity and employee satisfaction, organizations that want to bring service quality to the fore want to work with leaders who have ethical leadership characteristics. Taking into account the wishes and expectations of the members of the organization they work with, ethical leaders can be effective in creating an effective and productive working environment for the members of the organization. Ethical leaders, who make ethical decisions and act proactively as per universal principles in order to increase organizational efficiency, enable employees to work with higher performance. In conclusion, ethical leadership education should be included in the education of managers and they should be motivated to show ethical behaviour by using various incentives.